Mortality of physicians by COVID-19 according to their specialty, in the first and second wave of the pandemic in Peru - Villamonte-Calanche, Wilfredo (2023)
Introduction: COVID-19 is an infectious disease declared a pandemic by the WHO in March 2020. It has caused millions of deaths, including among doctors in the world. The objective was to determine the characteristics of physician mortality from COVID-19 and the specific mortality rate by specialty during the COVID-19 pandemic in Peru. Material and methods: Descriptive study that evaluated all deceased physicians reported by the Medical College of Peru until November 2021 and who complied with having their death certificate. Three groups were defined: specialist physicians with high (EMACC) and low (EMBCC) contact with COVID-19 patients and physicians without a specialty. Results: Age >60 years and males in the EMACC showed p=0.003 and 0.016, respectively. 69.4% of doctors died in Lima, and most died at Rebagliati Martins Hospital (21%). The highest specialty-specific mortality rate was 29.7 and 25.0 in epidemiology and health administration, respectively. In Lima, 69.4% of physicians died, mainly in the EMBCC group. Conclusion: Male physicians >60 years old are the ones who die more frequently, especially in the city of Lima and in the EMACC group. The highest mortality rates from COVID-19 were in the EMBCC group.